Analisis Pengaruh Kompetensi Aparat Sistem Pengendalian Internal Dan Partisipasi Masyarakat Terhadap Akuntabilitas Dana Desa Di Desa Lembur Barat Kecamatan Alor Tengah Utara Kabupaten Alor - Hasan, Ismawati Suhardi; Sabu, Junius Menase Sau; Maro, Yustina; tang, Sefnat Aristarkus (Jurnal Ilmiah Wahana Pendidikan, 2023)
Village fund accountability is an obligation to provide accountability or answer and explain the performance and action of a person/legal entity or the leadership of an organization to parties who have the right or authority to request information or accountability which consists of planning, implementing, administering, reporting and village financial accountability. This type of research is quantitative research with data collection techniques namely observation, interviews, and documentation studies. This study used primary data and the statistical method used in this study was multiple liniear regression with significant t tests and f tests as benchmarks for taking hypotheses. The results of this study indicate that: partially the competence of apparatus has an effect on the accountability of managing village funds in the village of overtime West, Alor Tengah Utara District, Alor Regency, as evidenced by the t test value of 0,044; partially the internal control system has an effect on the accountability of managing village funds in the village of overtime west, sub-district, as evidenced by the significant value of the t test of 0,000; partially community participation has an effect on the accountability of managing village of overtime west, sub-district of Alor Tengah Utara, Alor district, which is proven by a significant t-test value of 0,000; and simultaneously the competency variables of officials, internal control systems, and community participation have an effect on the accountability of managing village funds in the village of overtime west, Alor Tengah Utara district, Alor Regency which is proven with a significant value of the f test of 0,000